Hirudinea (Annelida) Fauna of Some Wetlands in Bingöl Province - Elaltunkara, Tuba; Koyun, Mustafa; Korkut, Nimetullah; Sağlam, Naim (Galenos Publishing House, 2022)
Objective: Leeches are important and reliable indicators of water quality and biodiversity in the ecosystem, so the presence of specific leech species is often closely related to basic water conditions and the presence of certain animals. This study was carried out in 2017 and 2018 in order to determine the Hirudinea fauna of some wetlands in Bingöl province. The investigation was conducted on a total of 13 stations. Methods: The water parameters of the stations were measured and recorded in situ. The collected specimens were brought alive to the Zoology Laboratory of Bingöl University Biology Department and kept alive under room temperature conditions. The diagnosis of leech samples was made through the living samples, and they were identified at the level of family, genus, and species. Results: During the study, seven species, belonging to six genera and in four families were recorded. These are; Hirudo verbana Carena, 1820, Glossiphonia complanata (L. 1758), Theromyzon tessulatum (O. F. Müller, 1774), Placopdella costata (Fr. Müller, 1846), Erpobdella octoculata (L., 1758), Erpobdella testacea (Savigny, 1820), Piscicola geometra (L., 1761). Conclusion: The locations where the study was carried out are new records for the detected leech species. © Telif hakkı 2022 Türkiye Parazitoloji Derneği.
Bingöl İlindeki Bazı Sulak Alanların Hirudinea (Annelida) Faunası
Keywords: annelida; Bingöl; fauna; Hirudinea; wetland